2008
DOI: 10.2337/db07-1329
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Counterregulatory Responses to Recurrent Hypoglycemia by Active Thalamic Inhibition

Abstract: OBJECTIVE-Hypoglycemia, the limiting factor in the glycemic management of diabetes, is the result of the interplay of therapeutic insulin excess and compromised glycemic defenses. The key feature of the latter is an attenuated sympathoadrenal response to hypoglycemia that typically follows an episode of recent antecedent iatrogenic hypoglycemia, a phenomenon termed hypoglycemia-associated autonomic failure (HAAF) in diabetes. We investigated the role of cerebral mechanisms in HAAF by measuring regional brain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 56 publications
4
90
0
3
Order By: Relevance
“…The thalamus acts as a relay between subcortical and cortical areas (13), and the hypothalamus is critical for fuel homeostasis and appetite control (1). Consistent with our findings, previous studies have demonstrated thalamic and hypothalamic activation under hypoglycemic conditions (14)(15)(16). The current data demonstrating oppositely directed modulation of PFC and brain reward center activation by circulating glucose support its role in stimulating executive control regions that exert inhibitory control of feeding behavior when glucose is available and promoting survival under hypoglycemic conditions by favoring instinctual motivation for food seeking and consumption when glucose is deficient.…”
Section: Discussionsupporting
confidence: 81%
“…The thalamus acts as a relay between subcortical and cortical areas (13), and the hypothalamus is critical for fuel homeostasis and appetite control (1). Consistent with our findings, previous studies have demonstrated thalamic and hypothalamic activation under hypoglycemic conditions (14)(15)(16). The current data demonstrating oppositely directed modulation of PFC and brain reward center activation by circulating glucose support its role in stimulating executive control regions that exert inhibitory control of feeding behavior when glucose is available and promoting survival under hypoglycemic conditions by favoring instinctual motivation for food seeking and consumption when glucose is deficient.…”
Section: Discussionsupporting
confidence: 81%
“…We also observed a reduced activation in left temporal lobe white matter, splenium and body of the corpus callosum of controls as compared with patients. While the involvement of these white matter areas is potentially interesting, the significance of the difference between the groups disappeared in such regions when a large cluster equal to that of other investigators was used for analysis, 1,4,6,7,12 in contrast to what observed in the thalamus. This observation raises questions about the robustness of the findings in the white-matter regions.…”
Section: Discussionmentioning
confidence: 96%
“…While some studies show less activation during hypoglycemia in several brain areas such as the amygdala and orbitofrontal cortex in patients with T1DM and hypoglycemia unawareness, 6 others have found thalamic activation to be greater during hypoglycemia in human models of HAAF. 7 In both studies, hypoglycemia-induced epinephrine secretion was noted to be reduced in the HAAF group, but direct correlation with regional activation was not reported.…”
Section: Introductionmentioning
confidence: 83%
“…Discussion of the various theories of the pathogenesis of this key feature of HAAF (1,36 -39) (the systemic mediator, brain fuel transport, and brain metabolism hypotheses) is beyond the scope of this perspective. While much of the neuroscience research into this issue has focused on the hypothalamus (37), recent translational research has raised the possibility that a complex cerebral network normally regulates the hypothalamic (and thus the sympathoadrenal) response to falling plasma glucose concentrations (38,39) and that an inhibitory signal mediated through the thalamus might be involved in the pathogenesis of HAAF (Fig. 3) (39).…”
Section: Mechanisms Of Haaf In Diabetesmentioning
confidence: 99%